2002
DOI: 10.1007/s00787-002-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Certain "repetitive" activities may not represent core features of autistic disorder and may be equivalent to normal motor and cognitive behaviors, as seen during typical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(59 citation statements)
references
References 36 publications
2
52
0
5
Order By: Relevance
“…That is, children with ASD demonstrated significantly more SIRS simultaneously (e.g., flapping while sighting, spinning while sighting) than the TD group. Previous studies have found that children with ASD demonstrate increasingly complex repetitive behaviors as they age (e.g., Bodfish et al, 2000;Militerni, Bravaccio, Falco, Fico, & Palermo, 2002), and our findings related to the simultaneous nature of SIRS align with these findings. The current findings demonstrate that complexity may be an important aspect of these behaviors that differentiates diagnostic groups and potentially contributes to exaggerated difficulties with participation for children with ASD and their families.…”
Section: Discussionsupporting
confidence: 90%
“…That is, children with ASD demonstrated significantly more SIRS simultaneously (e.g., flapping while sighting, spinning while sighting) than the TD group. Previous studies have found that children with ASD demonstrate increasingly complex repetitive behaviors as they age (e.g., Bodfish et al, 2000;Militerni, Bravaccio, Falco, Fico, & Palermo, 2002), and our findings related to the simultaneous nature of SIRS align with these findings. The current findings demonstrate that complexity may be an important aspect of these behaviors that differentiates diagnostic groups and potentially contributes to exaggerated difficulties with participation for children with ASD and their families.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, stereotyped motor movements, repetitive use of objects, unusual sensory interests and repetitive self-injurious behaviors are more commonly observed among lower-functioning individuals with ASDs. Conversely, repetitive speech and circumscribed interests are more commonly observed among higher functioning individuals with ASDs (Bishop et al, 2006;Cuccaro et al, 2003;Lam et al, 2008;Militerni, Bravaccio, Falco, Fico, & Palermo, 2002;Turner, 1999). These studies suggest that the relationship between RRBs and functioning level may vary depending on the type of RRB examined.…”
Section: The Diagnostic and Statistical Manual Of Mental Disorders Fmentioning
confidence: 99%
“…Other research indicates a different pattern of age-related differences in RRBs. In a comparison of younger and older children with ASD, younger children were more likely to exhibit motor and sensory repetitive behaviors, and older children were more likely to exhibit more complex repetitive behaviors (Militerni et al 2002). In another study of children with ASD who ranged in age from toddlers to 12 year olds, most RRBs, including self-injury, desire for sameness, restricted interests, and compulsions, were more frequent among the older than the younger children (Bishop et al 2006).…”
mentioning
confidence: 98%
“…Recent empirical work has suggested that there is considerable structure within the RRB domain, with as many as five different types of repetitive behavior (Lam and Aman 2007). Previous research has suggested that certain domains of repetitive behavior are associated with the presence of intellectual disability (ID), such as motor stereotypies, and others are associated with higher levels of cognitive functioning, such as repetitive speech (Bishop et al 2006;Militerni et al 2002). Other forms of RRB (such as insistence on sameness or the need for routines) have not been shown to be related to level of intellectual functioning (Militerni et al 2002).…”
mentioning
confidence: 99%